2020
DOI: 10.7717/peerj.8392
|View full text |Cite
|
Sign up to set email alerts
|

­Complete plastid genome sequences of two species of the Neotropical genus Brunellia (Brunelliaceae)

Abstract: Here we present the first two complete plastid genomes for Brunelliaceae, a Neotropical family with a single genus, Brunellia. We surveyed the entire plastid genome in order to find variable cpDNA regions for further phylogenetic analyses across the family. We sampled morphologically different species, B. antioquensis and B. trianae, and found that the plastid genomes are 157,685 and 157,775 bp in length and display the typical quadripartite structure found in angiosperms. Despite the clear morphological disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…The position of the COM clade within rosids has long been problematic in angiosperm phylogeny ( APG IV, 2016 ; Sun et al., 2016 ; Gonçalves et al., 2019 ). Our study showed that COM is monophyletic with strong support, a result that is consistent with most phylogenetic analyses based on plastid data (e.g., Gonçalves et al., 2019 ; Valencia-D et al., 2020 ) but conflicts with several studies using mitochondrial genes ( Zhu et al., 2007 ; Qiu et al., 2010 ) or nuclear data sets ( Zhao et al., 2016 ; Zeng et al., 2017 ; Yang et al., 2020 ). This phylogenetic discordance may be related to an ancient episode of hybridization followed by plastid capture during the rapid radiation of Rosidae ( Ruhfel et al., 2014 ; Sun et al., 2015 , 2016 ).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…The position of the COM clade within rosids has long been problematic in angiosperm phylogeny ( APG IV, 2016 ; Sun et al., 2016 ; Gonçalves et al., 2019 ). Our study showed that COM is monophyletic with strong support, a result that is consistent with most phylogenetic analyses based on plastid data (e.g., Gonçalves et al., 2019 ; Valencia-D et al., 2020 ) but conflicts with several studies using mitochondrial genes ( Zhu et al., 2007 ; Qiu et al., 2010 ) or nuclear data sets ( Zhao et al., 2016 ; Zeng et al., 2017 ; Yang et al., 2020 ). This phylogenetic discordance may be related to an ancient episode of hybridization followed by plastid capture during the rapid radiation of Rosidae ( Ruhfel et al., 2014 ; Sun et al., 2015 , 2016 ).…”
Section: Discussionsupporting
confidence: 70%
“…Trees tend to have lower Pi values compared with herbs ( Valencia-D et al., 2020 ). Similarly, our results showed that Pi values for both the coding and non-coding regions of the Averrhoa species were considerably lower than those of the Oxalis species ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…and B. trianae Cuatrec.) that were putatively distantly related, morphologically divergent, and classified in different sections of the genus (Valencia et al, 2020). However, as there was low variability (99.85% sequence similarity) between those plastomes, we decided to explore the use of nuclear loci here.…”
mentioning
confidence: 99%